PROFESIONALISME INTERNAL AUDITOR DAN INTENSI MELAKUKAN WHISTLEBLOWING - Devi Novita Sari; Herry Laksito (Diponegoro Journal of Accounting, 2014)
Many case of accounting violations that occur both in the country and abroad that reflect a professional attitude and ethical behavior of accountants are still worse. Such violations harm the users of financial statements. The purpose of this study is to analyze influence of the internal auditor’s professionalism did whistleblowing intentions. This study uses professionalism as an independent variable with five dimensions, consists of community affiliation, social obligations, dedication towards work, confidence in the rule itself or the community, internal auditors to be independent , and whistleblowing intentions as dependent variable.The population in this study is national banking company. Sampling method in this study is voluntary sampling. Case scenario will be given to internal auditors in central banks in Jakarta and then filed in and returned by the internal auditors who volunteered to fill in.The analysis showed that among the five dimensions of professionalism, community affiliation has no effect on whistleblowing intentions. This may be caused by a lack of self-awareness of internal auditors and the internal auditors are in a position of dilemma.